Comparative metagenomics indicates metabolic niche differentiation of benthic and planktonic Woeseiaceae - Tomeu Viver; Katrin Knittel; Rudolf Amann; Luis H. Orellana (Environmental Microbiome)
Abstract Background Benthic microbiomes exhibit remarkable temporal stability, contrasting with the dynamic, substrate-driven successions of bacterioplankton. Nonetheless, understanding their role in carbon cycling and interactions between these two microbial communities is limited due to the complexity of benthic microbiomes. Results Here, we used a long-reads (LRs) metagenomic approach to examine benthic microbiomes and compared them to the microbiomes in the overlaying water column and on particles, sampled at the same site and time off the island Heligoland in the North Sea. Although the diversity is vast in marine sediments, we recovered high quality metagenome assembled genomes (MAGs). Based on taxonomy and metabolic annotation of predicted proteins, benthic microbiomes are distinctly different from pelagic microbiomes. When comparing the 270 MAGs from free living and particle attached microbes from the water column to 115 MAGs from sediments only 2 MAGs affiliated to Acidimicrobiia and Desulfocapsaceae were shared at species level. Although, we recovered MAGs with the same taxonomic annotation in pelagic and benthic microbiomes, their metabolic potentials were different. A prominent example was the family Woeseiaceae that was among the most abundant taxa in the sediments. In benthic Woeseiaceae MAGs, we found polysaccharide utilization loci (PULs), predicted to target laminarin, alginate, and α-glucan. In contrast, pelagic Woeseiaceae MAGs were only recovered in the particle attached but not in the free-living fraction, and lacked PULs. They encoded a significantly more sulfatases and peptidases genes. Additionally, while genes involved in iron acquisition, gene regulation, and iron storage were widespread in Woeseiaceae MAGs, genes linked to dissimilatory iron reduction were mostly restricted to benthic Woeseiaceae, suggesting niche-specific adaptations to sediment redox conditions. Both, benthic and pelagic particle-attached Woeseiaceae MAGs encoded pilus TadA genes, which are essential for adhesion, colonization, and biofilm formation. Conclusions LR sequencing is currently the most valuable tool for analyzing highly diverse benthic microbiomes. The small overlap of MAGs from water column and sediments indicated a limited bentho-pelagic coupling. The data suggest that Woeseiaceae have habitat-specific metabolic specialization: while benthic Woeseiaceae possess the metabolic capabilities to utilize fresh organic compounds like laminarin derived from algae blooms, and to perform dissimilatory nitrate, nitrite and iron reduction for gain energy, particle attached Woeseiaceae from the water column may be specialized in degrading protein-rich and sulfated organic matter likely reflecting adaptation to the different types of organic matter and redox conditions in sediments vs. the water column.